2020
DOI: 10.3748/wjg.v26.i46.7287
|View full text |Cite
|
Sign up to set email alerts
|

Evolving role of artificial intelligence in gastrointestinal endoscopy

Abstract: Artificial intelligence (AI) is a combination of different technologies that enable machines to sense, comprehend, and learn with human-like levels of intelligence. AI technology will eventually enhance human capability, provide machines genuine autonomy, and reduce errors, and increase productivity and efficiency. AI seems promising, and the field is full of invention, novel applications; however, the limitation of machine learning suggests a cautious optimism as the right strategy. AI is also becoming incorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…Although the advantages of deep learning for the analysis of non-numerical data types is obvious, such as image data in endoscopy[ 39 - 41 ] and text or speech data in natural language processing[ 42 ], the utility of deep learning for the analysis of numerical data is less clear but remains promising. A recent study has demonstrated the utility of machine learning in predicting anti-TNF response in rheumatoid arthritis, but relied on genetic markers in addition to clinical data[ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the advantages of deep learning for the analysis of non-numerical data types is obvious, such as image data in endoscopy[ 39 - 41 ] and text or speech data in natural language processing[ 42 ], the utility of deep learning for the analysis of numerical data is less clear but remains promising. A recent study has demonstrated the utility of machine learning in predicting anti-TNF response in rheumatoid arthritis, but relied on genetic markers in addition to clinical data[ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Deep learning algorithms can often be regarded as a complete "end-to-end" system, so this kind of recognition method directly uses the convolution layer at the front end of the deep network to extract features and uses the output layer at the back end to classify them, so as to realize the recognition of lesion images. For example, Parasher et al [20] used GoogLeNet to extract features and classify gastrointestinal images at the same time. Veitch et al [21] used classical CNN to realize feature extraction and classification of narrow-band imaging enteroscopy images to identify colon polyp images.…”
Section: Discussionmentioning
confidence: 99%
“…Our VC model, trained using videos, could predict the tumor invasion depth more reliably and accurately than an image-trained model (IC v 2), as observed in the unedited video ( Videos S1 and S2 ). The role of AI during the endoscopic procedure is decision support [ 18 , 19 ]. If the AI can give us information about the exact invasion depth during endoscopy, the endoscopist can make a final decision to predict the invasion depth easily and rapidly.…”
Section: Discussionmentioning
confidence: 99%